PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENGEMBANGKAN KEMAMPUAN BAHASA ANAK KELOMPOK B DI TK RATNA KUMARA - Ratih Anak Agung (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Learning activities are carried out in schools, of course, a teacher uses learning models that are attractive to children so that the objectives of learning can be achieved. One of the learning approach models used is the scientific approach model. The scientific approach can help develop their own language because through this approach children are able to understand, recognize various materials using a scientific approach and also understand that information can come from anywhere and anytime. The problems that will be discussed include, what is the form of application, the obstacles faced and the efforts made to overcome the obstacles in the scientific approach for language development for group B children in Ratna Kumara Sari Kindergarten, Tonja Village, North Denpasar District, Denpasar City. This study aims to analyze the form of application, the obstacles faced and the efforts made to overcome the obstacles in the scientific approach for the development of the language of group B children in Ratna Kumara Sari Kindergarten, Tonja Village, North Denpasar District, Denpasar City. The theory used to analyze the problem is: Constructivism theory, the subjects of this research are the head of PAUD, homeroom teacher of group B, representatives of parents and children aged 5-6 years, data collection methods are non-participant observation, unstructured interviews and literature. The data that has been collected was analyzed using a qualitative descriptive analysis method with reduction steps, data presentation and drawing conclusions. The results showed (1) The application of a scientific approach in Ratna Kumara Sari Kindergarten through learning activities by developing language skills, can help children in mastering syllables and train children's courage in communicating (2) Constraints faced in the application of the scientific approach are caused by factors from the children themselves and from the surrounding environment (3) Efforts are made to overcome the obstacles faced, namely both teachers and parents must have synergistic cooperation in providing motivation and being a facilitator for the development of children's language skills.